Characterization of the murine Unp promoter. - Kilcup, Michael. (University of Ottawa (Canada), 1998)
Our lab is interested in the physiological role of the murine Unp proto-oncogene, a putative ubiquitin protease, which we postulate is involved in removing ubiquitin molecules from protein substrates, thereby preventing or delaying their degradation by the 26S proteasome. The work presented in this thesis describes the characterization of the Unp promoter and an analysis of Unp expression patterns in adult mice. Polymerase chain reaction (PCR)-mediated deletion mutagenesis was carried out using the full-length Unp promoter as a template and deletion constructs were designed by fusion of PCR products to the chloramphenicol acetyltransferase (CAT) reporter gene. Unp promoter deletions were subsequently transiently transfected into 293T human fibroblast cells and P19 murine embryonal carcinoma cells and promoter activity was assessed by CAT analysis. Transgenic mice were created that employed a 411 bp fragment of the Unp promoter driving expression of the E. Coli $\beta$-galactosidase reporter gene. Expression of the transgene was then assessed by Northern blot analysis as well as tissue sectioning and staining with 5-bromo-4-chloro-3-indolyl-$\beta$-D-galactopyranoside (X-GAL). (Abstract shortened by UMI.)
Keywords: Biology, Molecular.